Care dependency and management of urinary incontinence in nursing homes: A descriptive study. (4th December 2020) - Huion, Anja; De Witte, Nico; Everaert, Karel; Halfens, Ruud J.G.; Schols, Jos M.G.A.
Abstract: Aim: To explore the differences in managing urinary incontinence in residents in nursing homes aged 65 years or older in relation to their care dependency. Design: The 2015 data of the Dutch annual independent (Inter)national Prevalence Measurement of Quality of Care of Maastricht University were used. The design involved a cross‐sectional, multi‐centre point prevalence measurement in hospitals, care homes, and home care. Methods: Secondary data analysis on the data provided by care home organizations. Results: In the care independent group, the solely use of absorbing material was the mostly applied intervention. In the group of care dependent persons, the combination of absorbing material with toilet on set times and on individual basis was the most common approach. Conclusion: The outcome of this study indicated that the management of urinary incontinence in residents in nursing homes differs depending on their care dependency. Impact: Caregivers in nursing homes should be aware of preferences of residents regarding the management of their urinary incontinence. Researchers should investigate criteria used by caregivers and care receivers into the decision of the application of interventions for urinary incontinence. 摘要: 目的: 探讨65岁及以上养老院居民尿失禁管理与护理依赖的差异。 设计: 采用荷兰马斯特里赫特大学2015年年度国家 (国际) 独立护理患病状况衡量数据。设计涉及医院、疗养院和家庭护理中的横断面、多中心点患病状况衡量。 方法: 对疗养院机构提供的数据进行二次数据分析。 结果: 在独立护理组中, 单纯使用吸收材料是最常用的干预措施。在护理依赖者群体中, 最常见的方法是在固定时间和个别基础上采用吸收材料与厕所相结合的方式。 结论: 本研究结果表明, 养老院居民尿失禁的管理因其护理依赖性不同而有所不同。 影响: 养老院的照料人员应了解养老院居民在处理尿失禁方面的偏好。 研究者应调查照料人员和被照料人员使用的标准, 以决定是否采用尿失禁干预措施。